Genomic analysis of the emerging carbapenem-resistant Klebsiella pneumoniae sequence type 11 harbouring Klebsiella pneumoniae carbapenemase (KPC) in Oman - Mohammed Al Balushi; Rajesh Kumar; Azza Al-Rashdi; Amin Ratna; Ahood Al-Jabri; Neima Al-shekaili; Ramasandhya Rani; Sara Al Sumri; Laila Al-Ghabshi; Seif Al-Abri; Amina Al-Jardani (Elsevier, 2022)
Background and objective: The presence of carbapenemase enzymes among Enterobacterales is the main mechanism to reduce susceptibility to a wide range of antibiotics. Carbapenemase enzymes such as the Klebsiella pneumoniae carbapenemase (KPC) hydrolyse beta-lactam antibiotics group, which includes carbapenem, leads to fewer treatment options. We aim to describe the first report of carbapenem-resistant K. pneumoniae (CRKP) sequence type (ST) 11 harbouring KPC in Oman. Material and methods: Five confirmed CRKP isolates were isolated from clinical samples during the period of January 2019 till December 2019. Strains were genotyped by pulse field gel electrophoresis (PFGE) for genetic relatedness. Whole genome sequencing (WGS) was performed to observe relationships with global strains using multilocus sequence typing (MLST). Antimicrobial genes, capsular loci-K-types, plasmids types and virulence genes were also identified using whole genome sequence data. Results: All five CRKP were determined to have blaKPC-2 with or without blaOX-A48 and blaNDM-2. The molecular genotyping by PFGE showed 100% similarity among the five isolates. The MLST allelic profile analysis clonally clustered our strains with SL-258, CG-11 and ST11 mainly reported from South Asia. Further molecular characterization of the capsular K-locus and O-locus genes, revealed the strains to belong to KL-47 type and OL101 type respectively. The core genome typing suggests that our strains were clonally related to Chinese strains with less than five chromosomal nucleotides differences. Conclusion: Epidemiological and molecular analyses confirmed that these KPC-producing K. pneumoniae strains are from a single clone that caused multiple nosocomial infections in one health institution. This finding highlights the importance to sustain the surveillance and infection prevention efforts and to step up active screening to prevent the spread of nosocomial infection.